A apropriação do gênero textual artigo de opinião por alunos do 5º ano do ensino fundamental de uma escola da rede pública municipal de João Pessoa-PB por meio de sequência didática - Melo, Inayara Élida Aquino de (2023)
The present dissertation is the result of an intervention proposal based on a Didactic Sequence according to Dolz, Noverraz and Schneuwly (2004), based on the sequencing of teaching modules and structured in a systematic way, whose general objective of the investigation was focused on the written production of the textual genre opinion article about the social phenomenon "Child Labor", with 5th grade students of the Elementary School of a public school in João Pessoa-PB, in Portuguese Language classes, aiming the development of linguistic and argumentative skills and critical literacy. To walk the paths of this research, we based ourselves on several theorists, mainly in the studies of Bakhtin (1992, 2003, 2010); Marcuschi (2002, 2005, 2008); Koch and Elias (2003, 2006, 2012, 2017); Antunes( 2002, 2003); Freire(1996)in relation to the knowledge about the sociointeractionist perspective through language/language as artifacts of social use; for the approach on the didactic sequence we appropriate Dolz, Noverraz and Schneuwly (2004) and regarding the studies on the genre opinion article and argumentation we anchor scholars Beltrão (1980); Brakling (2000), Leal and Morais (2007) among other authors. The study also resorts to the documents, official guidelines in Brazil as the National Curricular Parameters (1998) and the Common National Curricular Base (2018). The qualitative approach and action research whose focus is the understanding and interpretation of social phenomena inserted in a context are the methodological guidelines of this research, in accordance with Bortoni-Ricardo (2008) and Thiollent (2011). As instruments of analysis, we used the textual productions of the written opinion articles of 10 (ten) students, whose analysis compared the initial production (IP) with the final production (FP) of the texts produced.